Integrated Glycome Strategy for Characterization of Aberrant LacNAc Contained N-Glycans Associated With Gastric Carcinoma - Yu, Hanjie; Li, Xiaojie; Chen, Mengting; Zhang, Fan; Liu, Xiawei; Yu, Jingmin; Zhong, Yaogang; Shu, Jian; Chen, Wentian; Du, Haoqi; Zhang, Kun; Zhang, Chen; et al. (Frontiers in Oncology, 2019)
Aberrant glycosylation is not only a feature of malignant cell transformation but also plays an important role in metastasis. In present study, an integrated strategy combining the lectin microarrays and lectin histochemistry was employed to investigate and verify the altered glycopatterns in gastric cancer (GC) cell lines as well as tumor specimens from matched tissue sets of 46 autopsy GC patients with the different stages. Subsequently, lectin-mediated affinity capture glycoproteins and MALDI-TOF/TOF-MS were also employed to acquire precise structural information of the altered glycans. According to the results, the glycopatterns recognized by 10 (e.g., ACA, MAL-I and ConA) and 3 lectins (PNA, MAL-I and VVA) showed significantly altered in GC cells and tissues compared to their corresponding controls, respectively. Notably, the glycopattern of Galβ-1,4GlcNAc (LacNAc) recognized by MAL-I exhibited significantly increased in GC cells (p<0.001) and tissues from patients at stage II and III (p<0.05), moreover, the high expression of this glycopattern is correlated with advanced stage (p<0.05) and lymphatic metastasis (p<0.001). The N-linked glycans from the glycoproteins in tissues from patients with advanced stage isolated by MAL-I-magnetic particle conjugates showed that the LacNAc contained N-glycan peaks increased dramatically, moreover, there were 10 neo-LacNAc-contained N-glycan peaks (e.g. m/z 1625.605, 1803.652 and1914.671) that were identified and annotated with proposed structures only in GC tissue with advanced stage. Among these neo-glycans, 5 and 2 N-glycans were modified with sialic acid or fucose based on LacNAc to form sialylated N-glycans or lewis antigens, respectively. Our results revealed that the aberrant expression of LacNAc is a characteristic of GC, and LacNAc may serve as a scaffold to be modified with sialic acid or fucose furtherly. Our finding provides useful information to reveal new molecular mechanism in the development of GC.